Carabids.org – a dynamic online database of ground beetle species traits (Coleoptera, Carabidae). Issue 3 (17th June 2013) - Homburg, Katharina; Homburg, Nils; Schäfer, Florian; Schuldt, Andreas; Assmann, Thorsten; Dytham, Calvin; Ewers, Robert
Abstract Carabids are a species‐rich group (more than 10 000 species in the Palaearctic region) and are intensively studied, inter alia due to their roles as bioindicators and mediators of nutrient flows in ecosystems. Numerous aspects of species' systematics, distribution, evolutionary biology (and phylogeny) and their ecology are well documented for the western Palaearctic and large data sets have already been compiled for macroecological studies. The online database carabids.org is an enhancement of these data sets and holds species classification and country level data on species distribution range for over 10 000 Palaearctic carabid species. Size and dispersal traits (body and eye size and hind wing development) are available for almost all (over 3400) western Palaearctic carabid species and ecological and life‐history traits (regarding food and habitat preferences as well as time of reproduction and activity) can be offered for most Central European (about 1000) species. Carabids.org is meant to be a collaborative and interactive project offering a variety of research opportunities. Our project contributes to the rapid expansion and analysis of freely available traits data on species‐rich invertebrates, which will help to advance our understanding of community assembly and functional diversity effects of such taxa across large spatial scales. We would very much appreciate data contributions from carabidologists, other scientists and interested parties.